The elderly adult: participation and identity - Zapata Farías, Hernán (Revista de Psicología, 2001)
In this article a review of the concept "Old age" and its significations are presented. It explains factors that involves accepting or rejecting this stage of life and analyses one of the most important factors related: That is, the lack of self acceptance of old aged people. In this article we put forward that this lack of acceptance starts a process of ’diffused identity?. This hypothesis is discussed and it makes the point that this process of diffusion of identity may be stopped by means of senior citizen participation and the achievement by old people of recognition by themselves and others as human persons with rigth and duties. Understanding that the meaning of personal identity-that is, that the one I was yesterday, the one I am now, and the one I will be tomorrow-would not be altered; what would indeed be modified is the social identity of senior citizens.